"Beyond the syllabus": Morris Isaacson High School's struggle for human equality under the Apartheid education system, 1958–1990. (3rd September 2021) - Glaser, Clive
ABSTRACT: The Bantu Education system, which replaced missionary-run black schooling in the mid-1950s, expanded schooling to accommodate the basic economic needs of the South African economy but it was done as cheaply as possible. The state paid teachers' salaries and in return it expected obedience and conformity from its employees. It was a tight-fisted, authoritarian education system, which stifled aspiration and human creativity. Yet, I want to argue in this paper, it unintentionally opened spaces which could nurture human ambition. I am not talking here about ambition merely for upward social mobility but for an assertion of humanity in the midst of a dehumanising social order. Morris Isaacson High School in Soweto was one of those spaces. I will show that Morris Isaacson, from the 1960s to the early 1990s, was a place where young people from mostly very poor backgrounds could aspire to be something more than an economic unit, where they could become creative and rounded human beings. Although the academic ethos of the school should not be underestimated, a variety of cultural, intellectual, and sports activities, which had no direct economic utility, enriched the lives of students and expanded their horizons.